Pengaruh Penerapan Model Pembelajaran Learning Cycle 5E terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Arinta Rara Kirana; Rahmawati, Fitriana; Nurashri , Partasiswi (Lentera: Jurnal Ilmiah Kependidikan, 2024)
The problem studied in this research is related to the less than optimal achievement of students' mathematical problem solving abilities. The aim of this research is to determine the effect of the 5E Learning cycle learning model on the mathematical problem solving abilities of class VIII Even Semester students at SMP Negeri 14 Bandar Lampung for the 2023/2024 academic year. This research uses an experimental method with the population in this research, namely all class VIII students of SMP Negeri 14 Bandar Lampung consisting of 8 classes. Meanwhile, two classes were taken as samples, namely class VIII B as the experimental class which applied the 5E Learning cycle learning model, and class VIII A as the control class which applied the conventional learning model. Samples were taken using the Cluster Random Sampling technique. To determine students' mathematical problem solving abilities, the author carried out a test in the form of an essay with five questions whose validity and reliability had first been tested. Hypothesis testing in this study used the t-hit formula and obtained a value of t = 3,10. From the t distribution table at the 5% significance level, it is known that t = 1,67, so , which means that the average mathematical problem solving ability of students who use the 5E Learning cycle learning model is higher than the average mathematical problem solving ability of students who use the model. conventional learning.